Reno-duodenal fistula as a complication of longstanding renal tract calculus. Issue 12 (31st December 2019) - Owen, William J; Folkard, Samuel S; Rohatgi, Ashish; Watson, Alan; Peters, John L
Abstract: We present a rare case detailing the investigations and subsequent treatment of a lady who presented with a reno-duodenal fistula and perinephric abscess as a complication of staghorn calculus and recurrent upper urinary tract infections. Treatment involved antibiotics, nephrostomy, endoscopic closure of the fistula tract with clips, radiological drain insertion and, ultimately, nephrectomy with primary omental patch closure of the duodenal defect. We discuss the incidence of fistula tract formation as a complication of staghorn calculi, as well as investigations and management strategies employed in the literature to treat such complications, which span from conservative treatment to nephrectomy and closure of the intestinal defect. We illustrate the post-operative complications such patients are prone to and discuss these in context of the case. Whilst such cases are rare clinicians should be vigilant for complications associated with chronic inflammatory processes occurring in the urinary tract and investigate accordingly.